GE_GERICHTE P/23149/2021 vom 22. Dezember 2021 - GE Cour de justice (2021)
SOUPÇON;RISQUE DE FUITE;VOL(DROIT PÉNAL);INFRACTION D'IMPORTANCE MINEURE;LARCIN;DIRECTIVE 2008/115/CE;CHANCES DE SUCCÈS;REJET DE LA DEMANDE | CPP.135; CPP.221; CP.139; CP.172ter; CP.291